The Business Propensity to Save - Hart, P. E. (Review of Economic Studies, 1962)
Journal Article The Business Propensity to Save Get access P. E. Hart P. E. Hart Bristol Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 29, Issue 2, February 1962, Pages 147–150, https://doi.org/10.2307/2295820 Published: 01 February 1962